Genomic Information for Clinicians in the Electronic Health Record: Lessons Learned From the Clinical Genome Resource Project and the Electronic Medical Records and Genomics Network - Williams, Marc S.; Taylor, Casey Overby; Walton, Nephi A.; Goehringer, Scott R.; Aronson, Samuel; Freimuth, Robert R.; Rasmussen, Luke V.; Hall, Eric S.; Prows, Cynthia A.; Chung, Wendy K.; Fedotov, Alexander; Nestor, Jordan; et al. (Frontiers in Genetics, 2019)
Genomic knowledge is being translated into clinical care. To fully realize the value, it is critical to place credible information in the hands of clinicians in time to support clinical decision-making. The electronic health record is an essential component of clinician workflow. Utilizing the electronic health record to present information to support the use of genomic medicine in clinical care to improve outcomes represents a tremendous opportunity. However, there are numerous barriers that prevent the effective use of the electronic health record for this purpose. The electronic health record working groups of the electronic MEdical Records and GEnomics network (eMERGE) and the Clinical Genome Resource (ClinGen) project, along with other groups, have been defining these barriers, to allow the development of solutions that can be tested using implementation pilots. In this paper, we present ‘lessons learned’ from these efforts to inform future efforts leading to the development of effective and sustainable solutions that will support the realization of genomic medicine.